El impacto del proyecto de yuca en la Costa Atlantica colombiana - Bode, P. (International Center for Tropical Agriculture, 1991)
The actual socioeconomic impact of the cassava natural drying project on the Atlantic Coast of Colombia is discussed with regard to increasing income of farmers and their families who live in the project's area of influence. Limitations in each phase of development of the project (pilot phase, 1st phase of expansion, consolidation phase, 2nd phase of expansion) are indicated. External circumstances in which the project has been carried out are also described, along with factors related to the organization of the project in small-farmer cooperatives and cassava production factors at the farm level. Ways in which this impact can be further improved are also discussed. The organization of these drying projects has proved to be an important mechanism for achieving a broader socioeconomic impact. Members of these organizations are the major beneficiaries of the project (high incomes through the sale of fresh cassava, participation in profits, employment in cassava drying). Farmers indirectly linked to the plants have been benefitted through the sale of cassava and the stimulus to production, which in turn generates a demand for employment. (CIAT)